Seizures and Interictal Epileptiform Activity in the Rat Collagenase Model for Intracerebral Hemorrhage - Germonpré, Charlotte; Proesmans, Silke; Bouckaert, Charlotte; Sprengers, Mathieu; Boon, Paul; Raedt, Robrecht; De Herdt, Veerle (Frontiers in Neuroscience, 2021)
AIMS Intracerebral hemorrhage (ICH) is a known risk factor for the development of acute symptomatic as well as late unprovoked seizures. The underlying pathophysiology of post-ICH seizures is incompletely understood and there are no reliable predictive biomarkers. An animal model to study post-ICH seizures is currently lacking. The aim of this study was to investigate 1) the occurrence of seizures and interictal epileptiform activity in the ICH rat collagenase model using long-term video-EEG monitoring (VEM) and 2) whether seizure occurrence was associated with interictal epileptiform activity and histological features. METHODS Male Sprague-Dawley rats were implanted with epidural electrodes. After one week of baseline VEM, collagenase was injected in left striatum to induce an ICH. VEM was continued for 180 days to assess the occurrence of post-ICH seizures and interictal epileptiform activity (spikes and epileptiform discharges). At the end of the experiment, animals were euthanized for histological characterization of the hemorrhagic lesion, using cresyl violet, Prussian blue and immunofluorescence staining. RESULTS Acute symptomatic seizures occurred in 4/12 animals between 46 and 80 hours after ICH induction. Late unprovoked seizures were present in 2/12 animals and started at 90 and 103 days post-ICH. Animals with late unprovoked seizures did not have acute symptomatic seizures. All electrographic seizures were accompanied by clear behavioral changes. Interictal spikes and epileptiform discharges were observed in all animals but occurred more frequently in rats with late seizures (p=0.019 and p<0.001, respectively). Animals with acute symptomatic seizures had more extended hemorrhagic lesions and hemosiderin deposits in the piriform cortex. CONCLUSION Both acute symptomatic and late unprovoked seizures were observed in the rat collagenase model. Interictal epileptiform activity was more frequently seen in animals with late seizures. Rats with acute symptomatic seizures showed more extensive lesions and hemosiderin deposits in the piriform cortex. This model could be used to further explore possible biomarkers for epileptogenesis.